Mycotoxin Contamination of Beverages Obtained from Tropical Crops - Granados Chinchilla, Fabio (2018)
This review is mainly centered on beverages obtained from tropical crops, including tea, nut milk, coffee, cocoa, and those prepared from fruits. After considering the epidemiological data found on the matrices above, the focus was given to recent methodological approaches to assess the most relevant mycotoxins. Aspects such as singularities among the mycotoxin and the beverage in which their were found, and the economic effects and repercussions that the mycotoxin-tainted ingredients have on the beverage industry were pointed out. Finally, the burden of their consumption through beverages, including risk and health effects on humans, was addressed as well.